Kebijakan Penanggulangan Stunting Di Indonesia - Latifa Suhada Nisa (Jurnal Kebijakan Pembangunan, 2018)
Indonesia has a high prevalence of stunting case, that is around 36%. Various efforts have been made by the government to tackle stunting problems through various policies, regulations and numbers of interventions. This paper aims to describe the policies and regulations that addressed the stunting problem in Indonesia. Indonesia already has a number of policies and regulations for stunting prevention, which is manifested in the form of specific and sensitive interventions. Specific interventions are carried out in the health sector by focusing on the first 1000 Days of Life (HPK) program, while sensitive interventions are carried out through providing access to clean water and sanitation. In addition to health, socio-economic factors are also known to affect stunting, such as poverty, education level, and family income. Stunting prevention requires crosssector cooperation and is carried out thoroughly. Policies and regulations that exist at the central level must also be followed by follow-up at the village level and involve not only the health sector but also other related sectors. The community-based response system needs to be improved, because of the high awareness of the community about the importance of balanced nutrition, environmental sanitation and hygiene is a big capital to reduce stunting rates. Abstrak Indonesia merupakan negara dengan prevalensi stunting yang tinggi, yaitu sekitar 36%. Berbagai upaya telah dilakukanpemerintah untuk menanggulangi masalah stunting me lalui berbagai kebijakan dan regulasi serta melalui sejumlah intervensi. Tulisan ini bertujuan untuk memaparkan kebijakan dan regulasi tentang penanggulangan stunting di Indonesia. Indonesia telah memiliki sejumlah kebijakan dan regulasi penanggulangan stunting yang diwujudkan dalam bentuk intervensi baik yang bersifat spesifik maupun sensitif.Intervensi spesifik dilakukan oleh sektor kesehatan dengan memfokuskan pada program 1000 Hari Pertama Kehidupan ( sedangkan intervensi sen sitif di antaranya dilakukan melalui penyediaan akses air bersih dan sanitasi. Selain kesehatan, faktor sosial ekonomi juga diketahui berpengaruh terhadap stunting, seperti masalah kemiskinan, tingkat pendidikan, dan pendapatan keluarga. Penanggulangan stu nting perlukerjasama lintas sektor dan dilakukan secara menyeluruh. Kebijakan dan regulasi yang ada di tingkat pusat, harus juga diikuti dengan tindak lanjut di daerah hingga tingkat desa dan melibatkan tidak hanya sektor kesehatan tetapi juga sektor terk ait lainnya. Sistem penanggulangan berbasis masyarakat perlu ditingkatkan lagi, karena kesadaran yang tinggi dari masyarakat akan pentingnya gizi seimbang, sanitasi dan kebersihan lingkungan merupakan modal yang besar untuk menekan angka stunting.